Is pulmonary capillary wedge pressure a reliable indicator of postcapillary pulmonary hypertension - KOCAKAYA, DERYA (My University, 2023)
Although current pulmonary hypertension (PH) guidelines recommend a pulmonary capillary wedge pressure (PCWP) above 15 mmHg for the detection of a post-capillary component, the rational of this recommendation may not be quite compatible with the peculiar hemodynamics of PH. We hypothesize that a high PCWP alone does not necessarily indicate left-sided disease and this diagnosis can be improved using LV transmural pressure difference (∆PTM). In this two-center, retrospective, observational study; we enrolled 1070 patients with PH who had undergone heart catheterization with the final study population comprising of 961 cases. ∆PTM was calculated as PCWP minus right atrial pressure. The patients with group II PH had significantly higher ∆PTM values (12.6 ± 6.6 mmHg) compared to the other groups (1.1 ± 4.8 in group I, 12.4 ± 6.6 in group II, 2.5 ± 6.4 in group III and 0.8 ± 8.0 in group IV, P<0.001) despite overlapping PCWP values. A ∆PTM cut-off of 7 mmHg identifies left-heart disease when PCWP>15 (area under curve, 0.825; 95% confidence interval, 0.784 to. 0.866; P<0.001). Five-year mortality was significantly higher in patients with high ∆PTM and PCWP subgroup compared to low ∆PTM plus high PCWP (26.1% vs. 18.5%, P=0.027), and low ∆PTM and PCWP subgroups (26.1% vs. 15.6%, P<0.001). ∆PTM has supplementary discriminatory power in distinguishing patients with and without post-capillary PH. In conclusion, a new approach utilizing ∆PTM may improve our understanding of PH pathophysiology and may identify a subpopulation who may potentially benefit from PH-specific treatments.
Keywords: heart failure; hemodynamics; pulmonary capillary wedge pressure; pulmonary vascular resistance; pulmonary hypertension